1987
DOI: 10.1002/hep.1840070615
|View full text |Cite
|
Sign up to set email alerts
|

Mucus hypersecretion in the gallbladder epithelium of ground squirrels fed a lithogenic diet for the induction of cholesterol gallstones

Abstract: This study identified mucus granules, determined mode of release and quantified their volume in the gallbladder epithelium of Richardson's ground squirrels (Spermophilus richardsonii) fed a lithogenic diet of 2% cholesterol to experimentally induce gallstone formation. Tissue was examined using light microscopy histochemistry, scanning and transmission electron microscopy, as well as autoradiography and morphometry at the electron microscopic level. Autoradiography demonstrated incorporation of a glycoprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Moreover, the enhancement of mucus secretion and an increase in mitosis before the formation of any precipitate have been described (Freston et al, 1969;Lee and Scott, 1982;Lee et al, 1981b;Pemsingh et al, 1987b;Putz and Willems, 1981;Scott, 1976). By using 3 H-glucosamine, Malet et al (1989) demonstrated that, in animals fed with a cholesterol-rich diet, mucin production increases twofold and sevenfold after 1 and 3 weeks, respectively.…”
Section: Role Of Gallbladder Mucus Secretion In Gallstone Formationmentioning
confidence: 90%
“…Moreover, the enhancement of mucus secretion and an increase in mitosis before the formation of any precipitate have been described (Freston et al, 1969;Lee and Scott, 1982;Lee et al, 1981b;Pemsingh et al, 1987b;Putz and Willems, 1981;Scott, 1976). By using 3 H-glucosamine, Malet et al (1989) demonstrated that, in animals fed with a cholesterol-rich diet, mucin production increases twofold and sevenfold after 1 and 3 weeks, respectively.…”
Section: Role Of Gallbladder Mucus Secretion In Gallstone Formationmentioning
confidence: 90%
“…The implication of mucin in gallstone formation has been widely studied. Hypersecretion of mucus occurs during gallstone formation in humans [6][7][8][9] and experimental animals [10]. Apart from forming the nucleus for calculus, the mucins form a structural component of gallstones as shown by histochemical studies on calculi [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, hypersecretion of gallbladder mucins is a prerequisite for gallstone formation, and increased amounts of gallbladder mucins are consistently observed in gallbladder bile of several animal models of gallstones (7)(8)(9). Also, mucins are found within cholesterol gallstones, where they act as a matrix for stone growth (10).…”
mentioning
confidence: 99%